Pengaruh Penguatan Moderasi Beragama Terhadap Sikap Toleran dan Prilaku Beragama Santri SMPIT Pondok Pesantren As-Syakur Kota Bengkulu - Anis Dian Mutiara (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to, 1) examine the effect of strengthening religious moderation on the tolerant attitudes of students at As-Syakur Islamic Boarding School in Bengkulu City; 2) examine the effect of strengthening religious moderation on students’ religious behavior. The research employed a quantitative non-experimental method with a correlational approach. Data were collected using questionnaires and analyzed through basic assumption tests, classical assumption tests, and hypothesis testing using simple linear regression with t-test and F-test. The results indicate that strengthening religious moderation has a significant effect on students’ tolerant attitudes, with a significance value of 0.027 (< 0.05). However, strengthening religious moderation does not have a significant effect on students’ religious behavior, as indicated by a significance value of 0.208 (> 0.05). In conclusion, strengthening religious moderation contributes to improving students’ tolerant attitudes but does not significantly influence their religious behavior at As-Syakur Islamic Boarding School, Bengkulu City.  Keywords: Religious Moderation, Religious Behavior, Tolerant Attitude